ChemInform Abstract: Fused Perovskite Tunnel Structures in Ba5Fe6+S4+O8 (0.44 ≤ x ≤ 0.55) with x‐Dependent Two‐Stage Magnetizations. Issue 43 (7th October 2016) - Wright, Taylor; Prots, Yurii; Valldor, Martin
Abstract: Polycrystalline samples of Ba5 Fe6+x S4+x O8 (x = 0.44—0.55) are prepared by solid state reaction of stoichiometric amounts of BaO, Fe2 O3 and S (Al2 O3 crucible in evacuated silica tubes, 800 °C, 70 h).